Graves' Disease as a Manifestation of Immune Reconstitution in HIV-Infected Individuals after Initiation of Highly Active Antiretroviral Therapy - Samad Rasul; Robert Delapenha; Faria Farhat; Jhansi Gajjala; Syeda Mehreen Zahra (AIDS Research and Treatment)
Graves' disease after the initiation of highly active antiretroviral therapy (HAART) in certain HIV-1-infected individuals has been described as an immune reconstitution inflammatory syndrome (IRIS). This phenomenon should be suspected in individuals who present with clinical deterioration and a presentation suggestive of hyperthyroidism despite good virological and immunological response to HAART. Signs and symptoms of hyperthyroidism may be discrete or overt and typically develop 8–33 months after initiating therapy. One to two percent of HIV-infected patients can present with overt thyroid disease. Relatively few cases of Graves' IRIS have been reported in the literature to date. We describe four cases of Graves' IRIS in HIV-infected patients who were started on HAART therapy.